Additive and non‐additive effects of day and night temperatures on thermally plastic traits in a model for adaptive seasonal plasticity - Rodrigues, Yara Katia (2021)
Developmental plasticity can match organismal phenotypes to ecological conditions, helping populations to deal with the environmental heterogeneity of alternating seasons. In contrast to natural situations, experimental studies of plasticity often use environmental conditions that are held constant during development. To explore potential interactions between day and night temperatures, we tested effects of circadian temperature fluctuations on thermally plastic traits in a seasonally plastic butterfly, Bicyclus anynana. Comparing phenotypes for four treatments corresponding to a full-factorial analysis of cooler and warmer temperatures, we found evidence of significant interaction effects between day and night temperatures. We then focused on comparing phenotypes between individuals reared under two types of temperature fluctuations (warmer days with cooler nights, and cooler days with warmer nights) and individuals reared under a constant temperature of the same daily mean. We found evidence of additive-like effects (for body size), and different types of dominance-like effects, with one particular period of the light cycle (for development time) or one particular extreme temperature (for eyespot size) having a larger impact on phenotype. Differences between thermally plastic traits, which together underlie alternative seasonal strategies for survival and reproduction, revealed their independent responses to temperature. This study underscores the value of studying how organisms integrate complex environmental information toward a complete understanding of natural phenotypic variation and of the impact of environmental change thereon.